PENGARUH REPUTASI PERUSAHAAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN (KASUS RUMAH SAKIT ISLAM IBNU SINA PEKANBARU) - Aryska, Metha; ", Kasmirudin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to look at the Effect of Corporate Reputation and Quality Service Patient Satisfaction (Case Islam Ibn Sina Hospital Pekanbaru). The study was conducted with descriptive analysis method, by collecting 100 questionnaires data then tabulated into a table that is further described systematically and to determine which variables are most dominant in determining patient satisfaction by using SPSS 21:00 as data processing tools. Rated R Square of 0.667 which indicates that customer satisfaction is able to be explained by the company's reputation and the quality of services by 66.7% while the remaining 33.3% is explained by other causes. The influence of the company's reputation and quality of service to positive patient satisfaction, which means that every increase in the implementation of the company's reputation and the quality of service it will cause an increase in the patient satisfaction.Keywords: Corporate Reputation, Quality Service, Patient Satisfaction